1908 N.Y. Laws 242, ch. 93, § 1 - (:unkn) unknown (General Publisher, 1908)
Prohibited possession of any slungshot, billy, sandclub, or metal knuckles. Prohibited possession of dagger, dirk, or dangerous knife with intent of harm. Violators guilty of a felony.
--
Keywords: POSSESSION - NON-GUN ARMS